Asuhan Keperawatan Jiwa: Pasien Resiko Perilaku Kekerasan - Deli Lita Anisa; Arif Setiya Budi; Suyanta Suyanta (Poltekkes Kemenkes Semarang, 2021)
Background: risk of Violent Behavior (RPK) is an angry response or vulnerable behavior carried out by someone where the behavior is at risk of endangering oneself, others, and the surrounding environment. There are two factors that influence the risk of violent behavior, namely predisposing factors and precipitation factors.Purpose: this study aims to describe how nursing care risks violent behavior.Methods: this study uses a qualitative method using a nursing process approach. The subjects in this study were 1 client at Risk for Violent Behavior.Results: the results of this study are the result of mental nursing care at the risk of social behavior through interventions to build a trusting relationship, help clients express their angry feelings, help clients reveal signs of violent behavior they experience, discuss with clients violent behavior committed, discuss with clients the consequences negative consequences of the act, discuss how to express healthy anger. Conclusion: the provision of nursing care to clients is adjusted to the client's problems and responses.